Acute Toxicity of Xylene on the African Catfish Clarias gariepinus - I.C. Davies; E.S. Erondu; A.I. Hart; L.C. Osuji (Journal of Applied Sciences and Environmental Management, 2019)
Acute toxicity of xylene on an African catfish (Clarias gariepinus) was carried out. A total of 210 catfish C. gariepinus juveniles with mean length 15.20±2.3cm, and mean weight of 10.23±2.6g were obtained from the University of Port Harcourt Demonstration Farm. The test was determined for 96hour median lethal concentration using concentrations of 250ml/l, 200ml/l, 150ml/l, 100ml/l, 50ml/l, 25ml/l and 0.0ml/l (control) which gave a LC50 value of 63.965ml/l with upper and lower confidence limits at 106.53 ml/l and 37.82ml/l respectively. The median lethal time LT50 recorded was 55.7 hours. There was a strong correlation between (%) mortality in Probits and the Log10 Dose (R²=0.9772). There was statistical significance (P>0.05) in the number of mortality observed in the six concentrations from 24 hours to 96 hours of exposure and high percentage mortalities were recorded as the concentration of the toxicant increased. No mortalities were recorded in the control. The cumulative mortality recorded after exposure of C. gariepinus to xylene was time dependent. Based on this the high percentage mortalities of the fish species it is therefore recommended that the use of this chemical be minimized and proper contingency plans be carried out before discharging this toxicants into the aquatic environment. Waste from this chemical and spill incidences should be detoxified to a less toxic level before disposing into the aquatic environment. The results obtained may provide valuable information for formulation of environmental policies and serve as a model for bio-monitoring of the aquatic environment.